2022
DOI: 10.15244/pjoes/153970
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Coliforms in Microplastic Associated Biofilm in Estuarine Ecosystem

Abstract: Coliforms and microplastic pollution are major issues prevailing in the estuarine ecosystem. At present, the Adyar river in Chennai, Tamil Nadu is under threat due to sewage disposal and solid waste dumping. In the present investigation surface water samples were collected from five sampling locations and analyzed for coliforms, microplastics (MPs), and the development of biofilm. The maximum coliform population of 75±6-228±12 MPN/100mL was observed during the pre-monsoon period. The MP content was in the rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…This is a health concern and releases MNPs (released when laundering from personal care products and products used in textile and plastic processing industries) into the environment. MNPs leaking from dilapidated wastewater facilities are washed into freshwater bodies through urban runoff [126,127]. Waste and treatment facilities must be continuously repaired and regularly serviced to reduce these environmental leakages.…”
Section: Repairs and Maintenance Of Waste Facilitiesmentioning
confidence: 99%
“…This is a health concern and releases MNPs (released when laundering from personal care products and products used in textile and plastic processing industries) into the environment. MNPs leaking from dilapidated wastewater facilities are washed into freshwater bodies through urban runoff [126,127]. Waste and treatment facilities must be continuously repaired and regularly serviced to reduce these environmental leakages.…”
Section: Repairs and Maintenance Of Waste Facilitiesmentioning
confidence: 99%
“…This releases MNPs directly to aquatic environments. Dharmaraj et al observed coliforms associated with fecal matter on MP from the Adyar river [101], showing how sewage leaks release MNPs into water bodies [102].…”
Section: Mnps From Water Runoffmentioning
confidence: 99%